Environmental noise in urban and periurban green areas of a micro basin in Heredia, Costa Rica. (UNED Research Journal, 2020)
Introduction: One of the manifestations of environmental impacts caused by urbanization is noise pollution, related to the presence of unwanted sound levels caused by human activities. These affects wildlife with discomfort, stress, and other harmful effects and might even include physical damage. Objective: To analyze the noise present in peri-urban and urban green areas adjacent to the micro basin of the Bermúdez River, in Heredia, Costa Rica. Methods: We installed Audiomoth automated recording equipment in six sampling sites along the micro basin. Three study sites were established in the peri-urban area and three in the urban area. Devices were programmed to record 1 minute every 10 minutes for 24 hours over 6 continuous days, twice per site. The Noise Index (SPL1) was used to evaluate the recorded sounds through sound pressure measurements. Results: The average noise levels in the urban area were significantly higher than in the peri-urban area (V=3 383 238, p
Keywords: Enviromental noise; Ecoacoustics; Urban ecology; Micro-basin; Audiomoth